The Impact of Media Representation on Female Athlete Identity and Self-Perception - Şahin, Ayşe; Soylu , Dilek; Toktas, Elif; Köse, Neşe (International Journal of Sport Studies for Health, 2024)
Objective: This study explores the impact of media representation on female athlete identity and self-perception. Methods and Materials: A qualitative research design was employed, utilizing semi-structured interviews to collect data. Twenty-four female athletes, aged 18 to 35, from various sports disciplines in Istanbul participated. The interviews, conducted in Turkish, lasted between 60 to 90 minutes and were transcribed verbatim. Thematic analysis was performed using NVivo software, allowing for the identification of key themes and subthemes related to media representation, identity construction, self-perception, and coping mechanisms. The study continued data collection until theoretical saturation was achieved. Findings: Thematic analysis revealed four main themes: media representation, identity construction, self-perception, and coping mechanisms. Participants reported stereotypical portrayals emphasizing physical appearance and emotional attributes over athletic skills. Media visibility was significantly lower for female athletes compared to their male counterparts, impacting their professional identity and opportunities. The internalization of stereotypes and media-driven body ideals affected their self-esteem and body image, contributing to performance anxiety and mental health challenges. Participants employed various coping mechanisms, including resilience building, support networks, media literacy, advocacy, and personal strategies, to manage the negative impacts of media representation. Conclusion: Media representation profoundly influences female athletes’ identity and self-perception, often reinforcing stereotypes and cultural biases. Equitable media coverage focusing on athletic achievements and personal stories is crucial for fostering positive self-identity among female athletes. Practical steps, including media training, advocacy, and promoting media literacy, are essential to create a more inclusive and supportive media environment.